2015
DOI: 10.1111/opo.12247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of education and diagnostic modes on glaucoma assessment by optometrists

Abstract: The study highlighted the importance of combining both structural and functional assessments in glaucoma. Current imaging technology demonstrated limited usefulness for event diagnosis due to the persistent difficulties of defining structural and functional loss in glaucoma, thus highlighting the need for new glaucoma assessment techniques. Short-term didactic teaching programs may only result in limited improvement of glaucoma diagnostic ability in optometrists, and hence, it may need to be combined with long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…However, the false negative rate was high (46%). These results were similar to the findings of a study of Australian optometrists using 2D disc observations . Since the original diagnoses of glaucomatous optic neuropathy was based on dilated indirect ophthalmoscopy, it is possible that diagnostic accuracy may have improved with 3D visualisation.…”
Section: Discussionsupporting
confidence: 85%
“…However, the false negative rate was high (46%). These results were similar to the findings of a study of Australian optometrists using 2D disc observations . Since the original diagnoses of glaucomatous optic neuropathy was based on dilated indirect ophthalmoscopy, it is possible that diagnostic accuracy may have improved with 3D visualisation.…”
Section: Discussionsupporting
confidence: 85%
“…These were defined as at least two of the following: (1) retinal changes characteristics of glaucoma were present on fundoscopy; (2) retinal changes characteristic of glaucoma were present on OCT imaging; or (3) patients exhibited visual field defect consistent with these structural findings. 8,35 If deemed appropriate by the ophthalmologist, the patient was referred for further comprehensive clinical consultation with a glaucoma specialist (KM) and included in the glaucomatous group if a final diagnosis of glaucoma was established. All glaucomatous subjects in this study were initiated on topical antiglaucoma medication following the consultation and their pretreatment IOPs were recorded.…”
Section: Study Participantsmentioning
confidence: 99%
“…3,4 However, discordance between structural and functional aspects is commonly observed 5,6 and may hinder the early clinical detection of glaucoma. 7,8 Hence, the relationship between GC population (structure) and visual sensitivity (function) in glaucoma has been an ongoing topic of investigation.…”
mentioning
confidence: 99%
“…Improvement of follow‐up of the Centre for Eye Health report recommendation was the only concern . A more recent CFEH‐based study found the concordance between glaucoma subspecialists and a group of optometrists classifying patients into those with confirmed glaucoma, those with suspected glaucoma and those without glaucoma, displayed high concordance, although there was room for improvement in combining imaging information in the diagnosis . Despite the availability of services offered by organisations such as the Centre for Eye Health, referral analysis indicates that not all optometric practice modes use the Centre: over 85 per cent of just over 5,000 annual optometric referrals are derived from practitioners who could be designated as ‘independent’.…”
Section: Models Of Integration For Optometrists and Future Challengesmentioning
confidence: 99%